2021
DOI: 10.1108/cms-03-2020-0118
|View full text |Cite
|
Sign up to set email alerts
|

Unpacking the chain mediation process between transformational leadership and knowledge worker creative performance: evidence from China

Abstract: Purpose This paper aims to draw upon motivated information processing theory to examine the sequential mediating roles of perspective taking and boundary spanning between transformational leadership and the creative performance of knowledge workers. Design/methodology/approach The study was carried out on a sample, including a dyad of 398 knowledge workers and their immediate supervisors in four research institutes in southwest China. The authors tested the theoretical model using structural equation modelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 64 publications
3
5
0
Order By: Relevance
“…For example, in a coaching leadership style, an executive who coaches instead of scolding his collaborators creates an effective work environment that aims at personal development rather than an immediate work-related task. The leadership style of a KWr can enhance engagement and promotes the creative ability of the team (Chen et al, 2020;Gumusluoglu & Ilsev, 2009;Wadei et al, 2021). Edelbroek et al (2019) studied the relationship between transactional and transformative leadership and revealed that transformational leadership competencies positively affect innovation and engagement enhanced by creativity.…”
Section: Social and Emotional Skillsmentioning
confidence: 99%
“…For example, in a coaching leadership style, an executive who coaches instead of scolding his collaborators creates an effective work environment that aims at personal development rather than an immediate work-related task. The leadership style of a KWr can enhance engagement and promotes the creative ability of the team (Chen et al, 2020;Gumusluoglu & Ilsev, 2009;Wadei et al, 2021). Edelbroek et al (2019) studied the relationship between transactional and transformative leadership and revealed that transformational leadership competencies positively affect innovation and engagement enhanced by creativity.…”
Section: Social and Emotional Skillsmentioning
confidence: 99%
“…For instance, senior employees find it relatively harder to invest more in work than younger employees, and new employees can perceive TL easier than experienced employees; wise leaders should notice the diversity of employees and try to influence them with suitable treatments. Hence, there is no doubt that creative employee performance is extremely positive for LO (Wadei, Lu, & Wu, 2021) in the coming post-COVID-19 era, when enterprises can only offer limited monetary incentive methods, by internalizing the values of corporations and employees, TL can effectively improve employees’ satisfaction and WE.…”
Section: Discussionmentioning
confidence: 99%
“…Given that leaders are of great importance in fostering boundary-spanning activities ( Mell et al, 2022 ), considerable attention has been given to their potential role in stimulating subordinate boundary-spanning behavior. For example, leaders’ supportive coaching behaviors provide a necessary support to help subordinates engage in boundary-spanning behavior ( Marrone et al, 2022 ), and charismatic and transformational leaders also endorse subordinate boundary-spanning activities ( Knipfer et al, 2018 ; Wadei et al, 2021 ). However, prior work has not underscored the potential risks to subordinates from carrying out boundary-spanning behavior, such as role overload ( Kahn et al, 1964 ; Katz and Kahn, 1978 ) and even leaders’ undermining ( Mell et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Second, our research sheds light on an essential mechanism of psychological safety and integrates the humor literature and boundary-spanning literature at a level of detail that has previously been overlooked in both strands of literature. Scholars have primarily focused on the value of boundary-spanning self-efficacy ( Marrone et al, 2022 ) and perspective taking ( Wadei et al, 2021 ) in explaining the significance of leaders for boundary spanning according to its positive points. Our research complements this existing work by capturing how challenging and taxing boundary-spanning behavior can be for subordinates ( Marrone, 2010 ) and highlighting the role of psychological safety to explain the positive function of leader humor in addressing these negative points.…”
Section: Discussionmentioning
confidence: 99%